Molecular Dynamics Analysis of Hydrogen Diffusion Behavior in Alpha-Fe Bi-Crystal Under Bending Deformation - Saitoh, Ken-ichi; Koga, Haruka; Sato, Tomohiro; Takuma, Masanori; Takahashi, Yoshimasa (Applied Mechanics, 2024)
The hydrogen embrittlement (HE) phenomenon occurring in drawn pearlitic steel wires sometimes results in dangerous delayed fracture and has been an important issue for a long time. HE is very sensitive to the amount of plastic deformation applied in the drawing process. Hydrogen (H) atom diffusion is affected by ambient thermal and mechanical conditions such as stress, pressure, and temperature. In addition, the influence of stress gradient (SG) on atomic diffusion is supposed to be crucial but is still unclear. Metallic materials undergoing plastic deformation naturally have SG, such as residual stresses, especially in inhomogeneous regions (e.g., surface or grain boundary). In this study, we performed molecular dynamics (MD) simulation using EAM potentials for Fe and H atoms and investigated the behavior of H atoms diffusing in pure iron (α-Fe) with the SG condition. Two types of SG conditions were investigated: an overall gradient established by a bending deformation of the specimen and an atomic-scale local gradient caused by the grain boundary (GB) structure. A bi-crystal model with H atoms and a GB structure was subjected to bending deformation. For a moderate flexure, bending stress is distributed linearly along the thickness of the specimen. The diffusion coefficient of H atoms in the bulk region increased with an increase in the SG value. In addition, it was clearly observed that the direction of diffusion was affected by the existence of the SG. It was found that diffusivity of the H atom is promoted by the reduction in its cohesive energy. From these MD results, we recognize an exponential relationship between the amount of H atom diffusion and the intensity of the SG in nano-sized bending deformation.